CONCEPT AND MEANING OF BAITURRAHMAN GRAND MOSQUE BUILDING SEMARANG AS A GREEN PLACE OF WORSHIP AND SUSTAINABLE - Muhammad Viky Firmansyah; Zahrotul Muwahidah; Allizam Yahya; Ahmad Fauzan Hidayatullah (Border: Jurnal Arsitektur, 2024)
This study explains the innovative concept and meaning behind Baiturrahman Grand Mosque of Semarang, which aims to be a green and sustainable place of worship. Using qualitative research methods with phenomenology approach through in-depth interviews with mosque officials, architects, and residents, this research reveals how sustainability principles are integrated into MBS design. In addition, this study also analyzes the perception and understanding of the surrounding community towards the concept of green and sustainability in the context of worship. The findings of this study are expected to provide valuable insights into how to incorporate environmental and spiritual values in religious architecture, creating a balanced, harmonious, and sustainable environment for all parties involved. Furthermore, the research highlights the importance of community engagement in fostering a shared vision for sustainable development. By examining case studies and best practices, the study aims to provide practical recommendations for future projects. The results underline the potential of religious institutions in promoting ecological stewardship and enhancing the overall well-being of their communities.